2009
DOI: 10.1097/bcr.0b013e3181abffb6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Colistin in a Pediatric Burn Unit in Argentina

Abstract: The use of sulfomethate sodium colistin for the treatment of infections caused by multiple drug resistant (MDR) Gram-negative microorganisms were studied in a burn unit to evaluate the safety of this drug. A prospective chart review of pediatric patients treated with intravenous colistin in a tertiary burn unit between January 2005 and December 2006 was performed. Forty-five courses of intravenous colistin treatment administered to 45 children were evaluated in the study period. Fourteen patients (31%) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 11 publications
5
35
5
1
Order By: Relevance
“…A recent systematic review of literature revealed that most of the studies of colistin use that included only children have been published until late 1970s, and within these studies, there were many differences regarding administration route (i.e., intramuscularly) and dosage of colistin [9]. Reports on intravenous use of colistin in children without cystic fibrosis published after 2000 include very few cases [3,8,9,14,17,21,28,37,41]. In our study, one third of colistin courses included children aged less than 1 year.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…A recent systematic review of literature revealed that most of the studies of colistin use that included only children have been published until late 1970s, and within these studies, there were many differences regarding administration route (i.e., intramuscularly) and dosage of colistin [9]. Reports on intravenous use of colistin in children without cystic fibrosis published after 2000 include very few cases [3,8,9,14,17,21,28,37,41]. In our study, one third of colistin courses included children aged less than 1 year.…”
Section: Discussionmentioning
confidence: 62%
“…In our study, one third of colistin courses included children aged less than 1 year. Although there are three recent case series of intravenous colistin therapy in children, two of them studied pediatric burn patients only (older than 2 months of age) [8,14,37], a patient population that tends to have significantly altered pharmacokinetic profile compared to other patients [42]. The third recent case series included seven critically ill children older than 1 year [8].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sin embargo, no documentamos tales efectos en nuestros pacientes. 24,25 El uso de antimicrobianos locales está muy difundido, pero su eficacia es un punto de debate 26 y aparece como un factor de riesgo no independiente de infección de esta serie.…”
Section: Discussionunclassified